Resource Allocation, Evaluational Capacity Building M&E Results Utilization Among Community Based Organizations in Meru County in Kenya - Cavens Kithinji; Christopher Gakuu; Harriet Kidombo (European Scientific Journal, ESJ, 2017)
Building capacity for evaluation has become a big concern in the effort of ensuring that evaluations are meaningful. Part of this capacity includes making sure that M&E activities have resources needed to carry them out. This study sought to establish the influence of allocating resources for M&E activities on the utilization of M&E result at the project level in Kenya’s Meru County. The study used a mixed mode approach in methodology and it was both a descriptive survey and a cross-sectional survey and used both descriptive and inferential analysis of the data collected. The study sampled 186 respondents from a targeted population of 430 employees working in Non-Governmental organizations and other community based organizations in the county. The study showed that resources were allocated for various M&E activities to a great extent. The study also noted high level of M&E results utilization at project level by project employees and all the indicators of resources allocation had positive correlation with M&E result utilization. It was noted that for every unit increase in resource allocation, there was an increase of 26.1% in M&E result utilization score which is a percentage that would justify allocating resources for M&E activities by project organizations.